Necking in extrusion film casting: the role of macromolecular architecture - Pol, Harshawardhan V.; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Journal of Rheology, 2013)
Extrusion film casting (EFC) is used on an industrial scale to produce several thousand tons of polymer films and coatings. While significant research has been carried out on necking of films of viscoelastic melts in EFC, the influence of macromolecular chain architecture on the necking behavior is not yet fully understood. In the present research, we have explored experimentally and theoretically the effects of long chain branching and molecular weight distribution on the extent of necking during EFC. Polyethylenes of essentially linear architecture but having narrow and broad molecular weight distributions, and polyethylenes having long chain branching were used for experimental studies. The EFC process was analyzed using the one-dimensional flow model of Silagy et al. [Polym. Eng. Sci. 36(21), 2614-2625 (1996)] in which multimode molecular constitutive equations namely the ``extended pom-pom'' equation (for long chain branched polymer melts) and the ``Rolie-Poly (Rouse linear entangled polymers)'' equation (for linear polymer melts) were incorporated. We show that the model qualitatively captures the salient features of the experimental data thereby elucidating the role of chain architecture on the extent of necking. (C) 2013 The Society of Rheology. [http://dx.doi.org/10.1122/1.4788911]

Nonisothermal analysis of extrusion film casting process using molecular constitutive equations - Pol, Harshawardhan; Banik, Sourya; Azad, Lal Busher; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Rheologica Acta, 2014)
Extrusion film casting (EFC) is a commercially important process that is used to produce several thousand tons of polymer films and coatings. In a recent work, we demonstrated the influence of polymer chain architecture on the extent of necking in an isothermal film casting operation (Pol et al., J Rheol 57:559-583, 2013). In the present research, we have explored experimentally and theoretically the effects of long-chain branching on the extent of necking during nonisothermal film casting conditions. Polyethylenes of linear and long-chain branched architectures were used for experimental studies. The EFC process was analyzed using the 1-D flow model of Silagy et al. (Polym Eng Sci 36:2614-2625, 1996) in which the energy equation was introduced to model nonisothermal effects, and two multimode constitutive equations, namely the ``extended pom-pom'' (XPP, for long-chain branched polymer melts) equation and the ``Rolie-Poly stretch version'' (RP-S, for linear polymer melts) equation, were incorporated to account for the effects of polymer chain architecture. We show that the model does a better job of capturing the qualitative features of the experimental data, thereby elucidating the role of chain architecture and nonisothermal conditions on the extent of necking.
Keywords: Branched; Extrusion; Film; Linear; Necking; Nonisothermal; Polyethylene

Self-similar rupture of thin free films of power-law fluids - Thete, Sumeet Suresh; Anthony, Christopher; Basaran, Osman A.; Doshi, Pankaj (Physical Review E, 2015)
The rupture of a thin free film of a power-law fluid under the competing influences of destabilizing van der Waals pressure and stabilizing surface tension pressure is analyzed. In such a fluid, viscosity decreases with the deformation rate raised to the n - 1 power where 0 < n <= 1 (n = 1 for a Newtonian fluid). When 6/7 < n <= 1, film rupture occurs under a balance between van der Waals pressure, inertial stress, and viscous stress. When n < 6/7, however, the dominant balance changes: Viscous stress becomes negligible and the film ruptures under the competition between van der Waals pressure, inertial stress, and surface tension pressure.